A Postmodernist Rewriting Of Homer’s Penelope: Margaret Atwood’s The Penelopiad - Petruş Raluca-Andreea (Romanian Journal of English Studies, 2024)
The article analyses Margaret Atwood’s reinterpretation of the Ithacan queen, Penelope, the wife of Odysseus, taking into consideration the silence-voice interplay between the original female character and her postmodernist re-representation, Penelope 2.0, the protagonist of The Penelopiad. In the Canadian writer’s novel, Penelope’s voice gets empowered through narrative means. Her voice reaches its peak or highest degree of expression in Atwood’s The Penelopiad, namely due to its main character and narrator, Penelope 2.0. Considering that a female first-person narrator elaborates the novel’s narrative, the article demonstrates how Penelope 2.0 expresses her feelings and thoughts regarding a series of events which occurred in the original text of The Odyssey, events which she elucidates by offering direct, well-developed insight, without any constraints.